Turbulence - Szalay, David (Scribner, 2019)
A woman strikes up a conversation with the man sitting next to her on a plane after some turbulence. He returns home to tragic news that has also impacted another stranger, a shaken pilot on his way to another continent who seeks comfort from a journalist he meets that night. Her life shifts subtly as well, before she heads to the airport on an assignment that will shift more lives in turn. In this wondrous, profoundly moving novel, Szalay<U+2019>s diverse protagonists circumnavigate the planet in twelve flights, from London to Madrid, from Dakar to Sao Paulo, to Toronto, to Delhi, to Doha, en route to see lovers or estranged siblings, aging parents, baby grandchildren, or nobody at all. Along the way, they experience the full range of human emotions from loneliness to love and, knowingly or otherwise, change each other in one brief, electrifying interaction after the next.